Hypoplastic Left Heart Syndrome Practice Variation Across 31 Centres From 20 European Countries. An AEPC Imaging Working Group Study - Cantinotti, Massimiliano; Voges, Inga; di Salvo, Giovanni; Ortiz-Garrido, Almudena; Bharucha, Tara; Grotenhuis, Heynric; Sabate-Rotes, Anna; Cavigelli, Anna; Roest, Arno; Sendzikaite, Skaiste; Nolan, Oscar; Ramcharan, Tristan; et al. (European journal of pediatrics, 2025)
UNLABELLED: Despite significant advances in knowledge and the development of guidelines, the management of hypoplastic left heart syndrome (HLHS) remains highly variable. A structured questionnaire was circulated across European Association of Paediatric & Congenital Cardiology (AEPC) affiliated centres. The aims were to evaluate standards in pre-operative assessment, types of surgery, follow-up and medical practices in children with HLHS. Thirty-one centres from 20 countries completed the survey. Delivery of babies with HLHS occurred in co-located maternity hospitals in 74% of centres; 29% were planned for spontaneous onset of labour, while 54% decided on a case-by-case basis. The preferred initial palliation was a right ventricle-pulmonary artery conduit in 55% of cases, modified Blalock-Thomas Taussig shunt (mBTTS) in 35%, and hybrid in 15% of cases. Timing for Glenn varied from 3 to 6 months of age and preoperative examination varied greatly: 65% performed cardiac catheterization and only 19% performed cardiac magnetic resonance. Stage III palliation was performed at a highly variable interval (2-6 years of age), nearly always employing an extracardiac conduit. Fenestration was routinely performed in 61% and reserved for borderline cases in 39%. All the centers adopted warfarin for the first 3-12 months after Fontan completion, and continued if a fenestration was present, while in non-fenestrated aspirin was left by most centers (e.g. 68%). However, there was a high disparity in the use of heart failure medications (e.g. in interstage I-II 35% use ACE-inhibitors, and only 26% digoxin). Follow-up practice also varied widely with only 60% employing specific protocols. CONCLUSION: This first multi-centre European survey from 31 centres from 20 different European countries highlighted a high practice variation in HLHS management across all the stages of Single Ventricle (Fontan) palliation. Major variations pertained to pre- and post-surgical investigations, surgical strategy for stage I and III, medical treatment regimens, and follow-up programs. WHAT IS KNOWN: • Hypoplastic left heart syndrome (HLHS) remains one of the most complex and challenging congenital cardiac defects to manage. • Investigating the management of children with HLHS across different European centres can facilitate study of the most effective management strategies. WHAT IS NEW: • Significant variation in HLHS management were reported in relation to pre- and post-surgical examinations, surgical strategy at stage I and III, medical treatment regimens, and follow-up programs. • Greater standardisation of imaging and diagnostic evaluation, medical treatment and follow-up surveillance may improve outcomes for these vulnerable patients and warrants further study.
Keywords: Surveys and Questionnaires; novorozenec; Infant, Newborn; Infant; Humans; Variation; Management; kojenec; Palliative Care; Hypoplastic Left Heart Syndrome; dítě; Child; Imaging; Female; lidé; Europe; syndrom hypoplazie levého srdce; průzkumy a dotazníky; předškolní dítě; Congenital heart disease; ženské pohlaví; Practice; paliativní péče; Practice Patterns, Physicians'; lékařská praxe - způsoby provádění; Hypoplastic left heart syndrome; Child, Preschool; Evropa